Expression Characterization of Flavonoid Biosynthetic Pathway Genes and Transcription Factors in Peanut Under Water Deficit Conditions - Kubra, Ghulam; Khan, Maryam; Munir, Faiza; Gul, Alvina; Shah, Tariq; Hussain, Adil; Caparrós-Ruiz, David; Amir, Rabia (Frontiers in Plant Science, 2021)
Drought is one of the hostile environmental stresses that limit the yield production of crop plants by modulating their growth and development. Peanut has a wide range of adaptations to arid and semi-arid climate, but its yield is prone to loss due to drought. Other than beneficial fatty acids and micronutrients, peanut harbors various bioactive compounds including flavonoids that hold prominent position as antioxidants in plants and protect them from oxidative stress. In this study, understanding of biosynthesis of flavonoid in peanut under water deficit condition was developed through expression analysis, correlational analysis and determining the accumulation pattern of phenols, flavonols and anthocyanins. Six peanut varieties (BARD479, BARI2011, BARI2000, GOLDEN, PG1102, PG1265) having variable response against drought stress have been selected. Higher water retention and flavonoid accumulation has been observed in BARI2011 but downregulation has been observed in the expression of genes and TFs which indicated the maintenance of normal homeostasis. Analysis of variance (ANOVA) revealed that the expression of flavonoid genes and transcription factor (TFs) is highly dependent upon the genotype of peanut in spatiotemporal manner. Correlation analysis between expression of flavonoid biosynthetic genes and TFs indicated the role AhMYB111 and AhMYB7 as inhibitor for AhF3H and AhFLS, respectively, and AhMYB7, AhTTG1 and AhCSU2 as positive regulator of the expression of Ah4CL, AhCHS, and AhF3H, respectively. However, AhbHLH and AhGL3 revealed no to little relation with the expression of flavonoid biosynthetic pathway genes. Correlational analysis between expression of TFs related to biosynthesis of flavonoids and the accumulation of phenolics, flavonols and anthocyanins indicated coregulation of flavonoid synthesis by TFs under water deficit condition in peanut. The study would provide insight to the role of flavonoid biosynthetic pathway in drought response in peanut and would aid to develop drought tolerant varieties of peanut.